Non Surgical Closure of Secundum Atrial Septal Defect by Percutaneous Transcatheter Amplatzer Septal Occluder - Abdullah, Hussein Abdul-Wahab M.; Alhammash, Sadiq M.; Kuraidi, Ali K.; Victor, Isam; AI-Quraishi, Muthanna H. (Journal of the Faculty of Medicine Baghdad, 2008)
Background:To assess the feasibility and early results of non-surgical transcatheter closure of atrial septal detect (ASD) using the Ampiatzer septal Occluder (ASO).Patients and Methods:From June 2003 to June 2005, i75 patients with ASD secundum, age range 3- 65 years, female to male ratio of 3:2. were evaluated for transcatheter closure using ASO at Ibn Al-Bitar Hospital for Cardiac Surgery. Transthoracic echocardiography was performed in al patients using standard suhxyphoid, apical, parasternal and suprasternal views. In allpatients, the procedure was done under general anesthesia.Results:Based on transesophageal echocardiography (TEE) Findings, 60 patients (33.7%) did not meet the criteria for transcatheter closure (40 females and 20 males). One hundredFifteen patients were found to have ASDs suitable for device closure. The device was successfully deployed in allpatients except 11 of them (104/115) (90.4%).In 11 cases with failure of ASO deployment, 6 patients had small floppy inferior rims which were not able to hold the device after the Minnesota wegeal maneuver. One adultpatient with a large ASD secundum and second degree AV block developed complete heart block during the procedure before the deployment of the occluder. One of them dislodgedinto the left atrium (LA) immediately after deployment because of a very small inferior rim and the other one dislodged into the LA because of descrewing of the cable after multiplemanipulations. Both of them were referred for surgery. An other one of the 11 patients had developed a thrombus in the LA during the procedure because of delay in giving heparinafter placing the guide wire in the left upper pulmonary vein. In the last patient, the procedure was abandoned and the occluder recaptured into the sheath before release fromthe cable because the TEE showed that the LA disc encroached on the mitral valve causing mitral stenosis.Conclusion:The transcatheter closure of secundum ASD is safe, efficacious with a very low rate of early and Sate complications. It is becoming an increasingly popular alternative to surgicalclosure.